Hubungan Mobilitas dengan Kualitas Hidup Domain Fisik pada Lansia - Maulina, Ema; Hadi W, Rita (Jurnal Keperawatan Soedirman, 2014)
Quality of life is a broad concept of scope is complex, influenced by a person's physical health, psychological, social, ability to function and economic factors. Reduced physical health can affect the level of ability of the mobility of the elderly in the fulfillment of their needs so that quality of life can’t be achieved with either. This research aimed to determine the relationship between level of mobility with domain of physical quality of life of elderly. This study used a non-experimental quantitative research design with descriptive-correlation type. The research used total sampling with 60 respondents. The data was collected by questioners Elderly Mobility Scale (EMS) and WHOQOL-BREF 26 item. The results of this research Showed that there is a relationship between levels of mobility capabilities with the domain of physical quality of life of elderly with Pearson correlation 0.416 and p value of 0.001 (p <0.05). The better the level of the ability of mobility and the domain of physical good quality of life as well. Nurses can be called on elderly for perform ROM in maintaining mobility and quality of life physical domain.